Diet quality among mothers and children in India: Roles of social and behavior change communication and nutrition-sensitive social protection programs - Nguyen, Phuong Hong; Neupane, Sumanta; Pant, Anjali; Avula, Rasmi; Herforth, Anna (Elsevier, 2024)
Objectives: Poor diets have been identified as one of major causes of mortality and morbidity worldwide. Limited evidence exists on the relationship of maternal and child diet quality and its determinants. We: 1) examined the agreement between maternal and child diet quality in India and 2) assessed the role of Social and Behavior Change Communication (SBCC) and nutrition-sensitive social protection (NSSP) programs on maternal and child diet quality.